1984
DOI: 10.1177/0265407584013005
|View full text |Cite
|
Sign up to set email alerts
|

Equity, Marital Satisfaction, and Stability

Abstract: Equity Theory, a social psychological theory concerned with fairness in interpersonal relations, has been shown to be predictivein casual encounters. Is it applicable in intimate relations as well? Newlyweds were asked a series of questions designed to measure the perceived level of equity in their relationship. Measures of their contentment/distress with the relationship and stability of the relationship were also taken. It was hypothesized that men and women who felt equitably treated would feel more content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 3 publications
1
33
0
1
Order By: Relevance
“…Garcia (1999) believes that satisfaction is considered at three levels: (a) the satisfaction with one's spouse, (b) satisfaction with family relationships, and (c) general satisfaction with life. Some researchers have focused on the relationship between stability and marital satisfaction (Givertz, Segrin, & Hanzal, 2009;Utne, Hatfield, Traupmann & Greenberger, 1984) and equity and marital satisfaction (Davis, Emerson, & Williams, 1997;Saginak & Saginak, 2005). A satisfactory relationship is the most important and complex aspect of intimate relationships.…”
Section: Marital Satisfactionmentioning
confidence: 99%
“…Garcia (1999) believes that satisfaction is considered at three levels: (a) the satisfaction with one's spouse, (b) satisfaction with family relationships, and (c) general satisfaction with life. Some researchers have focused on the relationship between stability and marital satisfaction (Givertz, Segrin, & Hanzal, 2009;Utne, Hatfield, Traupmann & Greenberger, 1984) and equity and marital satisfaction (Davis, Emerson, & Williams, 1997;Saginak & Saginak, 2005). A satisfactory relationship is the most important and complex aspect of intimate relationships.…”
Section: Marital Satisfactionmentioning
confidence: 99%
“…Some equity theorists suggest that equity is a social norm, thus overbenefited partners feel uncomfortable. Yet, research on extramarital affairs and relationship contentment (Hatfield, Greenberger, Traupmann & Lambert, 1982; Traupmann, Hatfield & Wexler, 1978) and research on newlyweds' marital satisfaction (Utne, Hatfield, Traupmann & Greenberger, 1984) has found that overbenefited partners have levels of satisfaction and contentment more similar to partners in equitable relationships.…”
Section: Equity Theorymentioning
confidence: 99%
“…Research has shown that inequity has a negative impact on relational characteristics such as satisfaction in close friendships (Medvene, Teal, & Slavich, 2000) and in dating relationships (Dainton, 2003;Sprecher, 2001a), marital contentment and stability (Utne, Hatfield, Traupmann, & Greenberger, 1984), marital satisfaction (Van Yperen & Buunk, 1990), a husband's liking of his wife (Canary & Stafford, 1992), and satisfaction in parents' relationship with their children (Vogl-Bauer, Kalbfleisch, & Beatty, 1998). In addition, inequitably treated partners are less likely to engage in relationship maintenance than equitably treated partners (Canary & Stafford, 1992, 1993, 2001Dainton, 2003;Messman, Canary, & Hause, 2000;Vogl-Bauer et al, 1998).…”
Section: Equity Theorymentioning
confidence: 99%